Creating 'safe spaces': A qualitative study to explore enablers and barriers to culturally safe end-of-life care. (April 2023) - Gott, Merryn; Wiles, Janine; Mason, Kathleen; Moeke-Maxwell, Tess
Background: Internationally, efforts are being made to promote equity in palliative and end-of-life care for Indigenous peoples. There is a need to better understand the experiences of Indigenous service users and staff. Aim: To explore the views of Māori health practitioners and whānau (family group) caregivers regarding barriers and enablers to culturally safe palliative and end-of-life care. Design: A Kaupapa Māori qualitative study. Setting/participants: Interviews were conducted with 103 participants from four areas of the North Island of Aotearoa New Zealand. Participants comprised bereaved whānau (family) of Māori with a life limiting illness and Māori health practitioners. Results: Māori health practitioners undertake cultural and connecting work to promote culturally safe palliative and end-of-life care for Māori patients and their whānau. This work is time-consuming and emotionally and culturally demanding and, for most, unpaid and unrecognised. Non-Māori staff can support this work by familiarising themselves with te reo Māori (the Māori language) and respecting cultural care customs. However, achieving culturally safe end-of-life care necessitates fundamental structural change and shared decision-making. Conclusions: Our findings indicate that efforts to support equitable palliative care for Indigenous people should recognise, and support, the existing efforts of health practitioners from these communities. Colleagues from non-Indigenous populations can support this work in a range of ways. Cultural safety must be appropriately resourced and embedded within health systems if aspirations of equitable palliative and end-of-life care are to be realised.